Guest editorial special issue on applications of nanotechnology in electromagnetic compatibility (nano-EMC) - Hanson, G. W. (2013)
The papers in this special issue are grouped in the following main topics: carbon-based nanomaterials for EM shielding and absorbing; nanocrystalline ferromagnetic (NFM) materials for EM shielding; modeling of EM field interaction with nanomaterials; interconnects.